Radiation response in Deinococcus deserti: IrrE is a metalloprotease that cleaves repressor protein DdrO. Issue 2 (18th September 2014) - Ludanyi, Monika; Blanchard, Laurence; Dulermo, Rémi; Brandelet, Géraldine; Bellanger, Laurent; Pignol, David; Lemaire, David; de Groot, Arjan
Summary D einococcus bacteria are famous for their extreme radiation tolerance. The IrrE protein was shown to be essential for radiation tolerance and, in an unelucidated manner, for induction of a number of genes in response to radiation, including recA and other DNA repair genes. Earlier studies indicated that IrrE could be a zinc peptidase, but proteolytic activity was not demonstrated. Here, using several in vivo and in vitro experiments, IrrE from Deinococcus deserti was found to interact with DdrO, a predicted regulator encoded by a radiation‐induced gene that is, like irrE, highly conserved in Deinococcus. Moreover, IrrE was found to cleave DdrO in vitro and when the proteins were coexpressed in Escherichia coli. This cleavage was not observed in the presence of metal chelator EDTA or when IrrE contains a mutation in the conserved active‐site motif of metallopeptidases. In D. deserti, IrrE‐dependent cleavage of DdrO was observed after exposure to radiation. Furthermore, DdrO‐dependent repression of the promoter of a radiation‐induced gene was shown. These results demonstrate that IrrE is a metalloprotease and we propose that IrrE‐mediated cleavage inactivates repressor protein DdrO, leading to transcriptional induction of various genes required for repair and survival after exposure of Deinococcus to radiation.